Learners’ Perceptions and Preferences in Distance Learning in the New Normal Era - Pingol, Katrisha Faye G. (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2022)
The COVID-19 pandemic has forced many school shutdowns and pushed millions of learners out of the classroom, resulting in shifts in teaching-learning modalities. The study uses a descriptive quantitative design to explore learners’ preferences and perceptions of distance education. Through a convenient sampling technique, senior high school students were surveyed about their preferred study habits and learning practices and their feelings and insights toward distance education. The study found that low access to the internet and gadgets has been a great cause of worry for them. Despite the physical distance, students like to interact and maintain communication with teachers and peers and receive feedback about their work. However, learners are ambivalent about the conduct of regular synchronous classes. The majority also believe that distance learning is more difficult than the pre-pandemic setup. It is suggested that relevant educational stakeholders find ways to help students who struggled during this sudden shift in education.